IMPROVING THE PERFORMANCE OF SMEs IN SEMARANG CITY IN THE PANDEMIC COVID 19 - Misbakhul Arrezqi; Bagus Yunianto Wibowo; Eldes Willy Filatrovi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
With the announcement of the regional quarantine status by President Jokowi for the increasing outbreak of the corona virus, it will indirectly have an overall impact on the economy, especially for the middle and lower class. In this case the regulation stipulated by the Government in the Health Quarantine Law states that during the area quarantine, the basic necessities of life of people living in the quarantine area are the responsibility of the Government. The social welfare of the community here is related to health, household economic conditions, a sense of security, and a good quality of life. So that people who are faced with the Covid-19 pandemic can still fulfill their basic needs and carry out their social functions. However, under these circumstances, the performance of UKM is very slow and some even collapsed. This is what made researchers investigate more deeply about the performance of SMEs during the Covid 19 pandemic. The purpose of this study was to examine the effect of entrepreneurial orientation and organizational learning on the quality of strategic assets, and also the influence of strategic asset quality on business performance. This research was conducted on SME snacks in Semarang City, the respondents used were 150 respondents. The data are processed using Structural Equation Modeling (SEM) with the help of the Analysis of Moment Structure (AMOS) version 23.0 program. Based on the results of the analysis, it is concluded that the effect of entrepreneurial orientation on the quality of strategic assets shows a CR value of -0.338 and with a probability of 0.735, testing the effect of entrepreneurial orientation on business performance shows a CR value of 2.499 and with a probability of 0.012, testing organizational learning on the quality of strategic assets shows a value CR is 4.881 and with a probability of 0.001., Testing the effect of organizational learning on business performance shows a CR value of 1.351 and with a probability of 0.177, the effect of strategic asset quality on business performance shows a CR value of 2.067 and with a probability of 0.039. Keywords: Entrepreneurship Orientation, Organizational Learning, Strategic Asset Quality, Business Performance, SMEs, SEM